Dynamic competition of inflation and delamination in the finite deformation of thin membranes. Issue 33 (12th August 2019) - Benet, Eduard; Vernerey, Franck J.
Abstract : We show that blister growth is controlled by the competition between two instabilities: one inherent to the rubber and a second one pertaining to the adhesion. Understanding this phenomenon can be used to target a stable blister shape. Abstract : The mechanics of blister delamination and growth plays a major role in a diversity of areas including medicine (skin pathology and mechanics of cell membranes), materials (adhesive and fracture) or soft robotics (actuation and morphing). The behavior of a blister in this context is typically difficult to grasp as it arises from the interplay of two highly nonlinear and time-dependent processes: membrane attachment and decohesion from a substrate. In the present work, we device a simplified approach, based on experimental systems, to predict the deformation path of a blister under various conditions. For this, we consider the problem of a growing blister made of a rubber-like membrane adhered on a rigid substrate, and develop a theoretical and experimental framework to study its stability and growth. We start by constructing a theoretical model of viscoelastic blister growth which we later validate with an experimental setup. We show that blister growth is controlled by the competition between two instabilities: one inherent to the rubber, and a second one pertaining to the adhesion with the substrate. Using these concepts, we show that a "targeted" stable blister shape can be achieved by controlling two parameters: the thickness of the film and the inflation rate.